Radikalisme di Internet - Imam Fauzi Ghifari (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2017)
This article  to discuss the radical groups that exploit it through social media,  this matter take a very large role in providing information to the public,  especially young people will be radical ideology.  Given the fact that the recruitment of youth into radical organizations mostly done by using the internet.   Social media plays an important role in providing information to the public on the issues so that the public terpropaganda radicalism towards radical issues in spread through the media.  This fact is evidenced by a number of terrorist groups that use social media to media propaganda and build a special site as a medium to coordinate all activities related to the execution of terrorist acts.